The Influence of Population and Economic Growth on The Human Development Index in Kuningan West Java - Ipuk Widayati Widayanti (IAIN Syekh Nurjati Cirebon, 2024)
This study aims to investigate the impact of economic growth and population on the Human Development Index in Kuningan. This study aims to gain a deeper understanding of the extent to which economic growth and population affect the Human Development Index in Kuningan. The data used in this study is secondary data obtained from the Central Statistics Agency (BPS) during the period 2018 to 2023, covering 6 years. In this study, multiple linear regression methods were used to analyze the data. Research findings show that when economic growth increases by 1%, the human development index will decrease by 0.421795. This is due to the uneven distribution of economic growth in society, resulting in income inequality and difficulty in meeting the needs of a decent life. This finding also shows that if the population increases by 1%, it will reduce the human development index in Kuningan by 2.187595. This decline is caused by a lack of employment that is not proportional to population growth, which has the potential to result in high unemployment and a decrease in people's welfare.